2013
DOI: 10.1016/j.apgeochem.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of diffuse reflectance mid-infrared spectroscopy for the prediction of the concentration of chemical elements estimated by X-ray fluorescence in agricultural and grazing European soils

Abstract: Editorial handling by R. Fuge a b s t r a c tThe aim of this study was to develop partial least-squares (PLS) regression models using diffuse reflectance Fourier transform mid-infrared (MIR) spectroscopy for the prediction of the concentration of elements in soil determined by X-ray fluorescence (XRF). A total of 4130 soils from the GEMAS European soil sampling program (geochemical mapping of agricultural soils and grazing land of Europe) were used for the development of models to predict concentrations of Al,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Similar to other soil spectral studies (Kemper and Sommer, 2002;Wu et al, 2007Wu et al, , 2005, prediction of some elements appeared to be possible through association with Al and Fe, and not with chemical parameters SOC and pH (Table 4). Many of the elements in the current study that were correlated (R > 0.70) with Al and to a lesser degree Fe, are reflective of relationships reported by Soriano-Disla et al (2013a, 2013b in European agricultural soils. The elements showing high inter-correlation are mostly minor elements; Ce, Ga, Ge, Sc, Th, Ti, V, and W (Table 4).…”
Section: Vis-nir Mir and Pxrf Prediction Of Soil Propertiessupporting
confidence: 65%
See 1 more Smart Citation
“…Similar to other soil spectral studies (Kemper and Sommer, 2002;Wu et al, 2007Wu et al, , 2005, prediction of some elements appeared to be possible through association with Al and Fe, and not with chemical parameters SOC and pH (Table 4). Many of the elements in the current study that were correlated (R > 0.70) with Al and to a lesser degree Fe, are reflective of relationships reported by Soriano-Disla et al (2013a, 2013b in European agricultural soils. The elements showing high inter-correlation are mostly minor elements; Ce, Ga, Ge, Sc, Th, Ti, V, and W (Table 4).…”
Section: Vis-nir Mir and Pxrf Prediction Of Soil Propertiessupporting
confidence: 65%
“…† introduced into the soil library. Overall, this model averaging approach resulted in a much greater success in soil geochemical characterization compared with other studies of soil geochemical characterization (Reeves and Smith, 2009;Soriano Disla et al, 2013a, 2013b using the traditional approach of selecting the best-performing model from a single spectral method.…”
Section: Implications Of These Results For Large Scale Routine Soil Mmentioning
confidence: 96%
“…Soriano-Disla et al (2013) obtained good results for the prediction of total concentrations of Ca, Mg, Al, Fe, Ga, Si, and Na in soil as determined by X-ray fluorescence (XRF) in their development of PLSR models using DRIFT-MIR spectroscopy. The successful predictions of these elements are reported to have occurred because of major MIR-sensitive soil components such as clays, Al and Fe-oxides/oxyhydroxides and organic matter (Soriano-Disla et al, 2013). Soriano-Disla et al (2014) noted that the MIR spec- tral region does not have sufficient information to provide an accurate prediction of K in soils, especially for extractable K because the extractable fraction of K is influenced by factors that are not infrared active (e.g., the concentration of K + in soil solution).…”
Section: Prediction Of Soil Nutrient Availabilitymentioning
confidence: 99%
“…[9,10,[14][15][16] The analysis of MIR data for the soils in this work reflects this. PCA of the MIR data revealed that the spectra clustered according to location.…”
Section: Discussionmentioning
confidence: 95%